The Effect of digital marketing on buying interest in indihome products with the role of brand awareness as an intervening variable - Victor, Victor; Meitiana, Meitiana; Kristinae, Vivy; Aprilita, Aprilita (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
This study examines the influence of digital marketing on purchase intention for the IndiHome product, with brand awareness serving as an intervening variable. The study contributes to a deeper understanding of the effectiveness of digital marketing strategies in enhancing customer purchase intention and strengthening brand awareness. The research employs the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with a quantitative approach. Data were collected through a questionnaire distributed to 100 IndiHome customers in Palangka Raya. The results indicate that digital marketing has a significant impact on purchase intention, both directly and indirectly through increased brand awareness. These findings highlight the importance of effective digital marketing strategies in enhancing brand awareness and driving customer purchasing decisions. The implications of this study can assist PT Telkom in optimizing its marketing strategies to improve IndiHome's competitiveness in the telecommunications industry.